PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPAS SD GKPS 2 PEMATANGSIANTAR - Ristialam Eventina Situmorang; Rio Parsaoran Napitupulu; Jon Roi Tua Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Make-A-Match cooperative learning model on social studies learning outcomes on the topic of economic conditions in fifth-grade students at GKPS 2 Pematangsiantar Private Elementary School in the 2025/2026 academic year. The lack of varied learning strategies that stimulate student engagement was the primary motivation for this study. The Make-A-Match model was implemented to create an interactive learning environment through a matching game involving question and answer cards. The research method used a quantitative experiment with a One Group Pretest-Posttest design with 20 students. Data were collected through a validated multiple-choice objective test. The results showed a significant improvement in student learning outcomes; the average score jumped from 56.74 in the pretest to 91.26 in the posttest. Statistical analysis showed that the calculated t value (12.075) was greater than the t table, demonstrating the model's significant impact. It was concluded that the Make-A-Match model effectively increased student understanding and engagement. This model is recommended as an innovation for educators to create more dynamic and meaningful learning in the classroom. Keywords: Make A Match, Learning Outcomes, Science, Regional Economy, Elementary School